Impact of the ICT, LKT and TEP in the Formation of Language Students (Guaraní-Spanish Bilingualism and English Language) at National University of Itapúa (Journal on studies and research of academic knowledge, 2022)
This research deals with the impact produced by ICT, LKT and TEP in the formation of Language students (Guaraní-Spanish Bilingualism and English Language); whose general objective is to describe the impact of ICT, TAC and TEP on the training of language students (Guaraní-Spanish Bilingualism and English Language) at National University of Itapúa; and as specific objectives to determine the relevance of the use of ICT, LKT and TEP in the training of language students; to establish the importance of the use of ICT, TAC and TEP, by language professors; and to specify the importance of the use of ICTs, LKT and TEP to achieve a University 2.0. To carry out this research a mixed method with and exploratory-descriptive approach was utilised. The population was composed of students and professors of language courses as well as professionals in the area of Technology, Science or Computer Engineering. The most relevant results showed that language professors promote the use of ICTs to consolidate linguistic knowledge. Among the most common ICTs used are virtual platforms, tutorials, Power point and electronic books. Both professors and language students use multimedia resources for their learning and knowledge (LKT), which is heightened by the Covid-19 pandemic. However, according to the results regarding TEP, there is no evidence of collaboration and interaction among professors, students and faculty´s staff in creating new contents in a common virtual community. Therefore, it is proposed to stimulate self-learning through the use of virtual resources and to encourage the use of virtual libraries for greater participation in scientific research and social innovation.
Keywords: ICT; LKT; TEP; University 2.0